Malakoplakia prostate presenting as urinary retention: a report of two cases and review of the literature. Issue 7 (28th July 2021) - Subbaraya, Swaroop; Sawant, Ajit; Pawar, Prakash; Patil, Sunil
Abstract : Malakoplakia is a rare chronic inflammatory condition, which primarily occurs in genitourinary tract, with prostatic malakoplakia being extremely rare. We present two cases of acute urinary retention, with clinically firm nodular prostate and a raised serum prostate-specific antigen. Transrectal ultrasound-guided prostatic biopsy showed features of malakoplakia. There was a significant reduction of size of prostate on transrectal ultrasonography after 4 weeks of antibiotics. However, one patient had failed trial without catheter and was subjected to transurethral resection of prostate. The biopsy of the prostatic chips also showed features of malakoplakia. Other patient improved symptomatically after antibiotics and was managed conservatively. Both the patients are on regular follow-up and are asymptomatic. Prostatic malakoplakia presenting as urinary retention is very uncommon with around 12 cases in the literature. Recognition of prostatic malakoplakia is important because clinically it can masquerade prostatic malignancy. Treatment with antibiotics is necessary before subjecting the patients for surgery in patients with obstructive symptoms.